Acquisition of Structures at Syntax-Discourse Interface: Post-Verbal Subjects in L2 English - Mitkovska, Liljana; Bužarovska, Eleni; Stojanovska-Ilievska, Nataša (Theory and practice of second language acquisition, 2023)
The present study explores the acceptability of postverbal subjects by intermediate andadvanced L2 English learners with L1 Macedonian, a pro-drop Slavic language with richverbal morphology. The two languages differ regarding the distribution of subject-verb inversion(SVI): in Macedonian, it is a default pattern in thetic sentences, but English severelyrestricts SVI to specific contexts. To test the hypothesis that Macedonian learners encounterdifficulties in acquisition of English SVI because of crosslinguistic influence, a grammaticalityjudgement and correction task was administered to two groups of Macedonian learners ofEnglish and a control group of English native speakers. The results revealed that L2 learnersfind English VS sentences and VS + it-insertion examples more acceptable than the nativespeakers, but the performance of the advanced group is closer to the native speakers than tothe intermediate learners. Both non-native groups accept more readily inappropriate Englishsentences that conform to typical L1 structures.